The Impact of the use of Smart Materials on the Facades of Contemporary Buildings - Moffeq Alobeidi, Mayssa; Abdulrhman Alsarraf, Abdula (International Journal of Engineering and Technology, 2018)
The impact of the development of smart materials after the third millennium on the design process in order to produce more responsive architectural buildings adapted to the internal and external environment and the performance and comfort of its users, adding the tremendous potential for the level of architectural facades in contemporary buildings. The problem of research in the lack of clarity of the impact of the use of smart materials in the facades of contemporary buildings, so the importance of it in studying the impact of these materials on the production of contemporary architectural facades. The research aims at preparing a theoretical framework that deals with the definition, types, and importance of smart materials in architecture through studies related to this aspect of the smart materials used. Of the smart materials in the facades of contemporary buildings, it dealt with the analysis of a series of facades of contemporary buildings where smart materials are used, The research found a range of formal, climatic and technological influences.Â Â Â